Non-opioid medication in pain medicine. Issue 7 (July 2022) - Seth, Bharti
Abstract: The International Association for the Study of Pain defines pain as "an unpleasant sensory and emotional experience associated with actual or potential tissue damage or described in such terms of such damage." Analgesics can be broadly classified according to their role primarily on nociception as well as pain perception, both of which are intimately integrated to the pain experience. An understanding of the pain pathway is inherent to a good understanding of how therapeutic targets can act as analgesics. An overview is discussed in this article to understand the rationale for therapeutic intervention. Opioids are substances that act on opioid receptors to produce morphine-like effects. All other analgesics that do not produce analgesia through a primary effect on opioid receptors can be labelled as non-opioid analgesics (NOAs). This article will aim to provide an overview of the pain pathway in relation to the therapeutic targets for providing analgesia, commonly used NOAs and their brief introduction.